Gender Differences in the Outcome of Offspring Prenatally Exposed to Drugs of Abuse - Traccis, Francesco; Frau, Roberto; Melis, Miriam (Frontiers in Behavioral Neuroscience, 2020)
Despite great efforts to warn pregnant women that drugs of abuse impact development of the embryo and the fetus, the use of legal and illegal drugs by childbearing women is still a major public health concern. In parallel with well-established teratogenic effects elicited by some drugs of abuse, epidemiological studies show that certain psychoactive substances do not induce birth defects but lead to subtle neurobehavioral alterations in the offspring that manifest as early as during infancy. Although gender differences in offspring susceptibility have not been fully investigated, a number of longitudinal studies indicate that male and female progeny exposed in utero to drugs of abuse show different vulnerabilities to deleterious effects of these substances in cognitive, executive and behavioral domains. Here, we briefly review the existing literature focusing on gender differences in the neurobehavioral consequences of maternal exposure to drugs of abuse. Overall, the data strongly indicate that male exposed progeny are more susceptible than female to dysfunctions in cognitive processing and emotional regulation. However, insights into the mechanisms determining this natural phenomenon are not currently available.